Employee financial wellness programs: Opportunities to promote financial inclusion?. Issue 3 (2nd July 2020) - Despard, Mathieu R.; Frank-Miller, Ellen; Fox-Dichter, Sophia; Germain, Geraldine; Conan, Matthew
ABSTRACT: Employee financial wellness programs (EFWPs) are a new practice that may promote financial inclusion by making it easier for workers with low- and moderate-incomes (LMI) to access financial services. We examine the strengths and limitations of workplace financial counseling, credit-building services, and small-dollar loans, and describe community collaboration to promote employee financial wellness. Findings suggest that these services are reaching a population that experiences financial exclusion, though evidence is mixed concerning how these services help workers with LMI resolve key financial challenges. Community collaboration focused on employee financial wellness presents opportunities to advocate for higher wages and better benefits.